Kenelm Digby (and Margaret Cavendish) on Motion - Daniel Whiting (Journal of Modern Philosophy)
Motion—and, in particular, local motion or change in location—plays a central role in Kenelm Digby’s natural philosophy and in his arguments for the immateriality of the soul. Despite this, Digby’s account of what motion consists in has yet to receive much scholarly attention. In this paper, I advance a novel interpretation of Digby on motion. According to it, Digby holds that for a body to move is for it to divide from and unify with other bodies. This is a view of motion—as change in relations of parthood—that Alison Peterman attributes to Digby’s contemporary and acquaintance, Margaret Cavendish. Having shown that Digby’s presentation of the view predates Cavendish’s by more than a decade, I make a case that Digby’s work influenced Cavendish’s on this topic. In developing and defending my reading, I consider to what extent the Digbean account of motion and the arguments for it accord with the ideals of the mechanical philosophy emerging in the early modern period.